The Benefits of Self-Awareness and Attention in Fog and Mist Computing. - Preden, Jurgo S.; Tammemae, Kalle; Jantsch, Axel; Leier, Mairo; Riid, Andri; Calis, Emine (Computer (00189162), 2015)
Self-awareness facilitates a proper assessment of cost-constrained cyber-physical systems, allocating limited resources where they are most needed. Together, situation awareness and attention are key enablers for self-awareness in efficient distributed sensing and computing networks.